Pavilion, Wabaunsee County - Scribner, Eric (Kansas State University, The Chapman Center for Rural Studies, 2011)
The following passage is a historically backed re-creation of life in the rural Kansas township. I have done extensive research on the township of Pavilion as well as the surrounding area, and I have chosen to integrate facts with fiction in an effort to reconstruct the quotidian flow of life in Pavilion. This story is not based one specific event in the history of Pavilion. Instead it is a synthesis of actual events, along with real people and fictional creations. These have been intertwined in order to provide a comprehensive presentation of what it might have been like for a child of pioneering parents to reside in the railroad township of Pavilion in 1888.
Eric Scribner, “Pavilion, Wabaunsee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/64.
Keywords: Waubaunsee County; Manhattan; Pavilion; M.A.B. Railroad; Bismark; Harveyville